PERAN KEPALA SEKOLAH SEBAGAI INOVATOR DALAM MENINGKATKAN KINERJA SEKOLAH - Wahidin; Asep Saepul Hidayat (LPPM Universitas Cipta Mandiri, 2025)
This study was conducted using an exploratory descriptive method and a qualitative approach to the focus of the study of the development of the principal's role as an innovator in improving school performance. In accordance with the design of qualitative research steps, this study concluded that: (1) Low school performance is caused by: (a) low personal performance improvement process; (b) lack of respect for solutions to performance problem threats; (c) weak creativity in carrying out the process of change and renewal, therefore the role of the principal as an innovator is needed who is oriented towards improving performance, achieving goals and optimizing the quality of education; (2) The role of the principal as an innovator is essentially: (a) compiling and implementing or changing strategies in overcoming school performance problems; (b) compiling and implementing a certain form of renewal through a certain program as a form of problem-solving solution or accelerating the smooth implementation of school performance; (c) building cooperation with all school residents in building innovations for certain school work components that are needed; and (3) Development of the role of the principal as an innovator in improving school performance, based on the general condition of the school, including: (1) Becoming a motivator in carrying out work innovation; (2) building an innovator mentality for school residents; (c) building an entrepreneurial spirit of innovators among school residents. With the hope that efforts to innovate in work will become a culture of work quality for school residents.